SAFFRON AS AN ADJUVANT THERAPY IN ULCERATIVE COLITIS PATIENTS. (22nd January 2022) - Ashktorab, Hassan; Oppong-Twene, Philip; Maecker, Holden Terry; Chirumamilla, Lakshmi; Kibreab, Angesom; Nabi, Eiman; Laiyemo, Adeyinka; Brim, Hassan
Abstract: BACKGROUND: In the search for alternative or supplemental treatment for Ulcerative Colitis (UC), we studied saffron (Crocus Sativus) in a UC clinical trial, as an additional intervention to improve clinical manifestations of UC through its anti-inflammatory and anti-reactive oxygen species properties. METHODS: This study is an open-label single-center pilot study conducted at Howard University. Patients with UC (n=3) in remission with mild-moderate disease received 50mg of Saffron twice daily for a period of 8-weeks. Inflammatory markers CRP measured in serum, calprotectin in feces, and the others (TNFα, INFγ, IL-6, IL-2, IL-17a, and IL-10) from PMA/ionomycin stimulated PBMCs by CyTOF, at baseline compared to 8-weeks Saffron treatment. Partial Mayo scoring was used for clinical response, the health-related quality of life questionnaire (HQoL) along with Hamilton Depression Rating Scale (HDRS) was used to assess the patient's quality of Life as the primary endpoints. 16sDNA was performed on stool DNA for gut microbiome. RESULTS: Significant calprotectin improvement was noticed in 2 out of 3 patients receiving saffron after 8 weeks compared to baseline. There was an improvement of Partial Mayo Score, pro-inflammatory markers TNFα, INFγ, IL-6, IL-2, IL-17a decreased while anti-inflammatory IL-10 increased. A wash-out period of 8 weeks reversed the calprotectin improvement while the second cycle of saffron treatment restored the calprotectin improvement level after 8-week in the 2 patients enrolled in the washout period. There was no drug-related adverse event during the study. Saffron's effects on the gut microbiome composition in UC patients showed a decrease in gamma Proteobacteria, and enrichment in Ruminococcaceae. CONCLUSIONS: Saffron improved clinical response for the main UC indicator fecal calprotectin and in Partial Mayo Scores. We observed significant improvement in patient's symptoms such as abdominal pain, diarrhea, and rectal bleeding. Therefore, using saffron supplements, along with conventional medicines, may have beneficial impacts on UC patients and reduce the need for immunosuppressants in these patients.